Middle Ear and Eustachian Tube Mucosal Immunology - Massa, Helen M. (Mucosal Immunology, 2015)
Mucosal immune responses within the middle ear and eustachian tube generally provide an effective and efficient response to the presence of microbial pathogens, with approximately 80% of clinically recognizable middle ear infections resolved within 7 days. Particularly for young children aged less than 3 years of age, the proximity and direct connection of the middle ear, via the eustachian tube, to the nasopharynx provide increased risk of commensal bacteria and upper respiratory tract viruses infecting the middle ear. Mucosal immunological defense in the middle ear and eustachian tube utilizes a number of mechanisms, including physicochemical barriers of mucus and the mucosal epithelial cells and innate immune responses such as inflammation, cellular infiltration, effusion, and antimicrobial protein secretions, in addition to adaptive host immune responses. Recent advances in otopathogen recognition via microbial pattern recognition receptors and elucidation of complex signaling cascades have improved understanding of the coordination and regulation of the middle ear mucosal response. These advances support vaccine development aiming to reduce the risk of otitis media in children.